(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The healthcare landscape is rapidly evolving, driven in large part by advancements in technology. From electronic health records to telemedicine platforms, these innovations offer immense potential to streamline administrative processes, improve patient care, and enhance overall healthcare delivery. However, effectively integrating technology into healthcare administration requires careful navigation of various challenges and considerations. This article explores key strategies for successfully leveraging technology in healthcare administration, ranging from optimizing electronic health record systems to harnessing data analytics for informed decision-making. Additionally, it addresses potential pitfalls and offers insights into overcoming barriers to adoption. By embracing technology strategically, healthcare administrators can position their organizations for long-term success in an increasingly digital healthcare environment.